Analysis of Stress Factors and Workload on the Performance of Employees of the General Election Supervisory Agency of East Java Province - Asrotul Hikmah; Hadi Prayitno; Anita Dewi Prahastuti Sujoso (Gema Lingkungan Kesehatan, 2024)
The workload undertaken by General Election Supervisory Agency (Bawaslu) in overseeing the 2024 General Election includes proactive election supervision activities, being responsive to reports of alleged election violations, creating calendars and work tools for supervision, and strengthening the supervision of election supervisors for the integrity and professionalism of election organizers. Excessive workload results in work stress among Bawaslu officers, which impacts work performance. This study aims to analyze the factors of work stress and workload on the performance of employees within the General Election Supervisory Agency of East Java Province in the Tapal Kuda region. An observational analytic research design with a cross-sectional approach was conducted on 91 respondents. Multivariate analysis using multiple linear regression was employed to identify the factors of workload and work stress on the performance of Bawaslu employees in East Java Province. The results of the study showed that respondents experienced work stress and workload, which impacted the performance of Bawaslu employees (p<0.05). The observation of work stress and workload contributed 30.9%. This study provides information and recommendations to the General Election Supervisory Agency as a consideration in making policies related to stress, workload, and employee performance.